2009
DOI: 10.1063/1.3233656
|View full text |Cite
|
Sign up to set email alerts
|

Wave energy converter with enhanced amplitude response at frequencies coinciding with Swedish west coast sea states by use of a supplementary submerged body

Abstract: Citation for the original published paper (version of record):Engström, J., Eriksson, M., Isberg, J., Leijon, M. (2009) Wave energy converter with enhanced amplitude response at frequencies coinciding with Swedish west coast sea states by use of a supplementary submerged body. Physics, 106(6) The full-scale direct-driven wave energy converter developed at Uppsala University has been in offshore operation at the Swedish west coast since 2006. Earlier simulations have now been validated by full-scale experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…This have led to the idea of a point absorber system with two bodies, one acting as a surface buoy, extracting energy, while the lower is passive and adds the desired inertia. [10][11][12][13] It is important to have the two bodies a sufficient distance apart so as not to get destructive interference. All tests on the two body system (TBS) thus far have shown promising results on a theoretical level with a 60% absorption in irregular waves and a significant decrease in optimal load damping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This have led to the idea of a point absorber system with two bodies, one acting as a surface buoy, extracting energy, while the lower is passive and adds the desired inertia. [10][11][12][13] It is important to have the two bodies a sufficient distance apart so as not to get destructive interference. All tests on the two body system (TBS) thus far have shown promising results on a theoretical level with a 60% absorption in irregular waves and a significant decrease in optimal load damping.…”
Section: Introductionmentioning
confidence: 99%
“…All tests on the two body system (TBS) thus far have shown promising results on a theoretical level with a 60% absorption in irregular waves and a significant decrease in optimal load damping. 12 Laboratory experiments with adjustable inertia have shown to give a 60% power capture ratio in irregular waves. 2 The wave energy converter (WEC) concept named the Lysekil Project that is being developed at Uppsala University is a point absorber system with a direct-driven linear generator connected to a semi-submerged buoy.…”
Section: Introductionmentioning
confidence: 99%
“…This gives rise to a low-frequency resonant bandgap in which water waves are strongly reflected by the resonator array. Although the results are demonstrated using resonators of vertical bottom-mounted split tubes, they can be realized by other resonators such as damping buoys for ocean wave energy conversion [19][20][21][22][23]. For damping resonator arrays, it is found that the resonant bandgap can dramatically modify the absorption efficiency of water waves.…”
mentioning
confidence: 99%
“…Damping resonators, such as heaving buoys, can be applied to extract the ocean wave energy [19][20][21] and an array of damping resonators is regarded as a key part of future ocean wave power plants [22,23]. Here, we investigate the influence of the above resonant gap on the absorption spectrum of damping resonator arrays.…”
mentioning
confidence: 99%
“…Its value has a significant influence on the performance of the WEC. As shown in Figure 9a, the CWR is a function of the damping coefficient [35]. The peak value of CWR for the WEC under this sea state is approximately 26.6% when the damping coefficient is 290.0 kN·s/m.…”
Section: Performance Of the Npc Under More Sea Statesmentioning
confidence: 87%